Catalytic materials for direct synthesis of dimethyl carbonate (DMC) from CO2. (10th January 2021) - Zhang, Meng; Xu, Yonghang; Williams, Brandon L.; Xiao, Min; Wang, Shuanjin; Han, Dongmei; Sun, Luyi; Meng, Yuezhong
Abstract: The direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol is a green synthetic route owing to nontoxicity of starting materials and synthetic process. DMC is widely used as a nontoxic solvent, effective fuel additive, and synthetic intermediate in medicine, pharmaceutics, chemistry and other fields. The key challenge is to design efficient and stable catalysts, which mainly includes ionic liquids, alkali carbonates, transition metal oxides, heteropoly acids, supported catalysts. The problems of low yield and difficulties in experiments have not been fundamentally solved. Electro-assist synthesis that provides extra energy for CO2 activation is tried and membranes reactor that separates products in time to increase DMC yield is also studied. Dehydrant catalysts with in-situ hydration for water removal can significantly improve DMC yield and catalysts stability because chemical equilibrium shifts substantially and the catalysts deactivation by produced water poisoning is avoided. This direction will have a considerable breakthrough when appropriate combination of catalysts and dehydrant is obtained. Graphical abstract: The direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol is a green synthetic route owing to nontoxicity of starting materials and synthetic process. DMC is widely used as a nontoxic solvent, effective fuel additive, and synthetic intermediate in medicine, pharmaceutics, chemistry and other fields. The key challenge is to design efficient and stable catalysts, which mainly includes ionic liquids, alkali carbonates, transition metal oxides, heteropoly acids, supported catalysts. The problems of low yield and difficulties in experiments have not been fundamentally solved. Electro-assist synthesis that provides extra energy for CO2 activation is tried and membranes reactor that separates products in time to increase DMC yield is also studied. Dehydrant catalysts with in-situ hydration for water removal can significantly improve DMC yield and catalysts stability because chemical equilibrium shifts substantially and the catalysts deactivation by produced water poisoning is avoided. This direction will have a considerable breakthrough when appropriate combination of catalysts and dehydrant is obtained. Image 1